The Thinner the Better: Self‐Esteem and Low Body Weight in Anorexia Nervosa. (7th February 2012) - Brockmeyer, Timo; Holtforth, Martin Grosse; Bents, Hinrich; Kämmerer, Annette; Herzog, Wolfgang; Friederich, Hans‐Christoph
<x xml:space="preserve">Abstract</x> The aim of the present study was to examine the associations between self‐esteem, motive satisfaction, and body weight in acute (acAN) and recovered (recAN) inpatients with anorexia nervosa (AN) and in healthy controls. Both acAN and recAN showed lower levels of self‐esteem as compared with healthy controls but did not differ from each other. In acAN, decreased body weight was associated with increased self‐esteem. Satisfaction of an achievement motive but not satisfaction of a superiority motive mediated this association. No such correlations could be observed in the other groups. This is the first study to show an often assumed association between decreased body weight and increased self‐esteem in AN patients. These preliminary results strengthen the assumption that low body weight may foster self‐esteem in patients with acAN, mainly through the satisfaction of an achievement motive. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Message Self‐esteem should be focused very early in the treatment of AN since weight gain may deprive the patient of an important source of self‐esteem. Treatment interventions should be attuned to underlying motives of threatened self‐esteem; in AN patients, the enhancement of self‐esteem via weight loss seems to be rather fuelled by the satisfaction of an achievement motive than by the satisfaction of a superiority motive. Specific trainings to improve self‐esteem in AN patients seem to be promising as an add‐on to regular treatment.